Decision-Making Support Framework for Electricity Supply in Non-Interconnected Rural Areas Based on FAHP - Moreno, Christian; Ospino-Castro, Adalberto; Robles-Algarín, Carlos (International Journal of Energy Economics and Policy, 2022)
The implementation of electrification programs in non-interconnected rural areas in Colombia is a challenge for the country in order to reduce the social gap in these regions. This task is responsibility of the Mining and Energy Planning Unit (UPME), which has as challenges the implementation of renewable energy projects that allow diversifying the national energy matrix. For this reason, this paper proposes a support framework for multicriteria decision-making in the electricity supply of non-interconnected rural areas for the Colombian Caribbean Region. The multicriteria method of the Fuzzy Analytical Hierarchical Process (FAHP) was used, which allows the incorporation of a fuzzy triangular scale to improve the imprecision in the judgments made by experts. A hierarchical structure with 6 renewable energy alternatives, 4 criteria and 16 sub-criteria was designed, which allowed the implementation of a paired comparison survey that was answered by 10 experts from the region. The results obtained show the relevance of all alternatives, which is evidenced by a percentage difference of less than 5% between all the options. The best alternative was solar PV (20,27%). Regarding the criteria, the most relevant were economic (39,6%) and environmental (30,8%). The most relevant sub-criterion was the renewable fraction, related to the possible reuse of equipment (20,2%).